HUKUM INTERNASIONAL DALAM WILAYAH PERBATASAN NEGARA - Putra, Satria Kurniawan (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2022)
From the border issues between Indonesia and neighboring countries, then problems arise at the border, the fundamental question is whether there is a role for international law at the border and whether international law has a function in dealing with problems that arise at the border. In what context is the function of International Law applied? In fact, all areas on the border of Indonesia contain several aspects of very complex problems, both from a security and socio-economic perspective, which at any time could potentially pose a threat to the sovereignty of the State of Indonesia. Indonesia has established archipelagic sea lanes, which are one of the rights owned by the Archipelagic State as regulated in UNCLOS. This is then stated in Government Regulation no. 37 Years 2002 concerning the Rights and Obligations of Foreign Ships and Aircraft in Executing the Right of Archipelagic Sea Lanes Pass through Defined Archipelagic Sea Lanes. Air traffic for commercial flights is regulated by Air Traffic Control (ATC) in the Flight Information Region (FIR). The purpose of these arrangements is to prevent accidents between flights with one another. The Presidential Regulation that has been signed is Presidential Regulation of the Republic of Indonesia Number 109 of 2022 concerning Ratification of the Agreement between the Government of the Republic of Indonesia and the Government of the Republic of Singapore concerning Adjustment of Boundaries between Flight Information Region Jakarta and Flight Information Region Singapore.